Resources heuristic teaching activity geometric transformations in the pre-university level - Morales Carballo, Armando; Locia Espinoza, Edgardo; Salmerón Merino, Petra (Atenas, 2016)
This article describes a teaching strategy to promote education planning isometric transformation: translation, in the pre-university level. The methodological theoretical framework that underpins the work fall on the contributions on methodologies for problem solving procedures (Locia, E., Mederos, O. Morales, A. Rodriguez, J. M, and Sigarreta, J. M. (2014) heuristic devices (Torres, P. 2013) and use GeoGebra as a fundamental heuristic device. During development, it was identified that the use of software as a heuristic device favored identifying elements that allowed the assimilation process of translation.